Transbronchial cryobiopsies for the diagnosis of diffuse parenchymal lung diseases: expert statement from the cryobiopsy working group on safety and utility and a call for standardization of the procedure - Hetzel, Jürgen; Maldonado, Fabien; Ravaglia, Claudia; Wells, Athol U.; Colby, Thomas V.; Tomassetti, Sara; Ryu, Jay H.; Fruchter, Oren; Piciucchi, Sara; Dubini, Alessandra; Cavazza, Alberto; Chilosi, Marco; et al. (Respiration, 2018)
Transbronchial cryobiopsies (TBCB) have recently been introduced as a promising and safer alternative to surgical lung biopsy in the diagnostic approach to diffuse parenchymal lung diseases (DPLD). Despite a substantial and expanding body of literature, the technique has not yet been standardized and its place in the diagnostic algorithm of DPLD remains to be defined. In part, this reflects concerns over the diagnostic yield and safety of the procedure, together with the rapid spread of the technique without competency and safety standards; furthermore, there is a substantial procedural variability among centers and interventional pulmonologists. We report this expert statement proposed during the third international conference on “Transbronchial Cryobiopsy in Diffuse Parenchymal Lung Disease” (Ravenna, October 27-28, 2016), which formulates evidence- and expert-based suggestions on the indications, contraindications, patient selection, and procedural aspects of the procedure. The following 5 domains were reviewed: (1) what is the role of TBCB in the diagnostic evaluation of DPLD: patient selection; (2) pathological considerations; (3) contraindications and safety considerations; (4) how should TBCB be performed and in what procedural environment; and (5) who should perform TBCB. Finally, the existence of white paper recommendations may also reassure local hospital credentialing committees tasked with endorsing an adoption of the technique.
Gesehen am 14.01.2020